THE INDUSTRIAL ENGINEERING IDENTITY: FROM HISTORIC SKILLS TO MODERN VALUES, DUTIES, AND ROLES - Darwish, Hasan; Van Dyk, Liezl (The South African Journal of Industrial Engineering, 2016)
Over the past 100 years, engineering has sub-divided into tens of disciplines in an attempt to deal with the different problems arising from the wide spectrum of human endeavours. One particular field, however, arose from problems relating to industry, interdisciplinary integration, growth, balance, and connectedness. This field is known as industrial engineering (IE). Yet the IE identity and role, although useful, often remains vague. This article presents a review of the factors that made IE what it is today, as well as the fields differentiating the skills. It begins with a brief historical overview of the factors that shaped IE. More importantly, though, the article focuses on the modern identity (made up of the values, roles, and duties) of industrial engineers in the 21st century. This is done by showing that the long-standing cliché of industrial engineers being ‘jacks of all trades and masters of none’ has actually become ‘connected to all trades and masters of some’ due to a significant evolution of skills and identity. An industrial engineering identity (IE-ID) tree model is developed by extracting concepts and elements from existing identity models to give structure to the IE-ID model. The model is then populated with questions and answers arising from the literature review. To conclude, the future utility of such a model is anticipated.